PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI SMA NEGERI 1 MENTAYA HILIR UTARA - Sanjaya, Adi; Fahmi, Fahmi; Sapuadi, Sapuadi (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
The principal has a very important role in improving the professional competence of teachers. So the role of the principal is very much needed to help teachers become professional teachers in teaching to create superior schools and produce quality students in accordance with the school's vision and mission. This study aims to examine how the principal's planning and implementation in improving the professional competence of teachers at SMA Negeri 1 Mentaya Hilir Utara. This study uses descriptive qualitative research. The data collection techniques used are observation, interviews, and documentation. The informants in this study were the principal and vice principal of SMA Negeri 1 Mentaya Hilir Utara. The results of this study explain the role of the principal in improving the professional competence of teachers, especially in the planning and implementation of strategies carried out by the principal through the creation of work program plans, academic supervision and creating KOMBEL (study group) work programs for teachers so that they can improve the professional competence of teachers ABSTRAKKepala sekolah memiliki peranan yang sangat penting dalam meningkatkan kompetensi professional guru. Sehingga peran kepala sekolah sanggat dibutuhkan untuk membantu para guru agar menjadi guru yang professional dalam mengajar untuk menciptakan sekolah yang unggul dan menghasilkan siswa yang berkualitas sesuai dengan visi misi sekolah. Penelitian ini bertujuan untuk  mengkaji tentang bagaiamana perencanaan dan pelaksanaan  kepala sekolah dalam meningkatkan kompetensi professional guru di SMA Negeri  1 Mentaya Hilir Utara. Penelitan ini menggunakan penelitian kualitatif deskriptif. Teknik pengumpulan data yang digunakan adalah  observasi, wawancara, dan dokumentasi. Adapun yang menjai informan dalam penelitian ini adalah kepala sekolah dan wakil kepala sekolah  SMA Negeri  1 Mentaya Hilir Utara. Hasil penelitian ini menjelaskan tentang pera kepala sekolah dalam meningkatkan kompetensi professional guru terkhusus pada perencanaan dan pelaksanaan strategi yang dilkukan oleh kepala sekolah melalui pembuatan perencanaan program kerja, suvervisi akademis dan membuat program kerja KOMBEL (kelompok belajar) untuk para guru sehingga dapat meningkatkan kompetensi professional guru.